KREATIVITAS GURU PENDIDIKAN AGAMA ISLAM DALAM MENERAPKAN STRATEGI PEMBELAJARAN TERHADAP PENINGKATAN HASIL BELAJAR SISWA SMA NEGERI 1 WUNDULAKO - Lukman, Aulia (Jurnal Teknologi Pendidikan Madrasah, 2021)
Islamic Religious Education teachers as educators are not only limited to delivering religious material or knowledge to students, but Islamic Religious Education teachers are also responsible for guiding and directing students in improving their learning outcomes. So that the results obtained by students in Islamic Religious Education lessons can increase and achieve good results. By choosing the right strategy in accordance with the teaching materials from Islamic Religious Education teachers, it can certainly improve the learning outcomes of their students. The purpose of the study was to determine whether the creativity of Islamic religious education teachers in the use of learning strategies could improve student learning outcomes at SMA Negeri 1 Wundulako. The results showed that the learning outcomes of students were categorized as good, the average value of students was between 75-90 in accordance with the standard KKM score of 75. This is the effect of creativity in the use of appropriate and appropriate learning strategies and varies by religious education teachers. Islam, so that the subject matter can be well received by students and get satisfactory results.